Triangulation of madness, power and resistance in selected post-war American novels - Dashti, Sorour Karampour (2016)
This study aims to discover the triangulation of madness, power and resistance in selected post-war American novels, namely The Catcher in the Rye (1951) by J. D. Salinger, On the Road (1957) by Jack Kerouac, and The End of the Road (1958) by John Barth. It is hypothesized in this study that the protagonists of the novels represent different modes of madness and resistance and I aim to analyze how the protagonists react to pressures by the disciplinary power that attempts either to normalize them or cast them into asylums and alienation. Thus, I present three objectives, namely to examine the characters’ entanglement in the disciplinary power system of their society and their different reactions to the status quo, to explore the concepts of madness and a madman as reflected by the characters of the selected texts and to discover how the authors portray the characters’ resistance to the pressures the disciplinary power imposed on them. This approach allows for a textual analysis of the characters of the selected texts based on Foucauldian concepts of madness, power and resistance as the theoretical tool, where Foucault suggests that madness and sanity are socially constructed concepts created by the disciplinary power system to eliminate resistant individuals. My findings demonstrate that the selected authors present those concepts of madness, power and resistance through the characters’ portrayal of visible disagreement with their respective society’s cultural codes of conformity. Thus, the three selected authors share a similar way in depicting mad resisting individuals who respond to society’s disciplinary power through their conducts. However, my findings also reveal that, despite sharing this similarity, the selected texts exhibit different modes of madness and resistance to society’s disciplinary power. For example, the protagonist of The Catcher in the Rye, Holden is regarded as mad because of his resistance to accept his society’s disciplinary codes. Thus, in terms of the triangulation of madness, power and resistance, Holden’s resistance to disciplinary power is portrayed as madness. On the other hand, Sal and Dean, the protagonists of On the Road, give birth to a new resistance strategy against the 1950s American cultural codes by transfiguring the dichotomy of madness and sanity, where their resistance to accept the disciplinary cultural codes of their society is depicted as madness that actually brings real happiness and prosperity to them. Thus, madness becomes a strategy for Sal and Dean to resist their society’s norms that are established by the disciplinary power system. Hence, the triangulation of madness, power and resistance in On the Road is Sal and Dean’s madness as resistance to society’s disciplinary power. In contrast, Jake, the protagonist of The End of the Road, resists the popular culture and mainstream values of the society by getting paralyzed; thus, he is entangled in the psychiatric power from which he has no way of freedom. Conversely, Joe, another major character in the text, is portrayed as a sane character whose obsession in gaining power and his resistance to society’s network of power relations manipulate the concept of madness. Joe resists his position in the network of power and decides to deconstruct the structure of the network by bringing Jake under his control. Thus, in the triangulation of madness, power and resistance, I posit the view that, in The End of the Road, the relation is madness to gain power in order to resist disciplinary system. Therefore, my findings show that the triangular relationship between Foucauldian concepts of madness, power and resistance is attained from the selected authors’ depictions of the different modes of madness and resistance to society’s powerful disciplinary norms.